Acquired perioral cutaneous Langerhans cell histiocytosis. - Khedim, N.; Hali, F.; El Fatoiki, F.Z.; Chiheb, S. (European Journal of Pediatric Dermatology, 2022)
LCH is an inflammatory neoplasm consisting of cells derived from medullary precursors, which usually have mutations of the MAPK signaling pathway (1). The spectrum of LCH is extremely large ranging from a single lesion affecting a single organ, generally bone or skin, to generalized multisystem lesions. The prognosis of the disease is also extremely variable, ranging from spontaneous resolution in a few months in the forms affecting only one organ to death in a few weeks in the multisystem forms with organ dysfunction.